Analysis of Financial Reporting Errors and Their Impact on Stakeholder Trust - Zakaria, Zakaria (Advances in Management & Financial Reporting, 2025)
Purpose: This study systematically examines the relationship between financial reporting errors and their impact on stakeholder trust. It will focus on the types and intensity of errors and explore strategies for trust recovery after identifying mistakes. Research Design and Methodology: The research employs a Systematic Literature Review (SLR) method, analyzing existing studies on financial reporting errors, their effects on stakeholder trust, and the mechanisms for regaining trust post-error. The review encompasses both mature and emerging markets, providing a global perspective. Findings and Discussion: The analysis reveals that intentional financial reporting errors, such as manipulation, cause significantly more significant damage to stakeholder trust than unintentional errors like technical mistakes. The severity of the errors also plays a crucial role in determining the level of trust erosion. Effective recovery strategies, including transparency, stakeholder engagement, and governance reforms, are essential for restoring trust. However, even with corrective actions, companies may not fully regain the same confidence level, especially following severe or high-profile errors. Implications: This study offers practical insights for corporate governance by highlighting the need for robust internal controls and transparent communication to address financial reporting errors. Companies can use these findings to develop strategic approaches that minimize the long-term damage to stakeholder trust and ensure more effective recovery after identifying financial discrepancies.